RANCANG BANGUN SISTEM INFORMASI ABSENSI PERANGKAT DESA BERBASIS WEBSITE DENGAN TEKNOLOGI GLOBAL POSITIONING SYSTEM(GPS) DI KANTOR DESA KADUNGORA - Ranti, Sopia; Nugraha, Yopi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of information technology has accelerated the digitalization of government administration, including the management of village officials' attendance. Conventional attendance systems, such as manual records and fingerprint-based systems, still have limitations, including inefficient data recapitulation and the inability to verify users' locations during attendance. This study aims to design and develop a web-based attendance system for village officials by utilizing Global Positioning System (GPS) technology and applying the Waterfall development method. The proposed system is capable of validating users' locations during attendance, managing attendance data, and generating integrated attendance reports. The results indicate that the system improves the accuracy of attendance recording, simplifies the monitoring process, and enhances the effectiveness of village administrative management.